Implementasi Strategi Pemasaran Dalam Upaya Peningkatan Nilai Jual Hasil Produksi Warga Binaan Pemasyarakatan - Agung Risaldo (Program Studi Manajemen Universitas Muslim Maros, 2021)
Correctional as an institution that aims to form prisoners and inmates become the whole person, In its implementation implement two coaching programs which are the first coaching personality and the second coaching self-reliance development. In the development of self-reliance in correctional institutions in Indonesia, implementing programs aimed to improve the ability of the prisoners. Prisoners are trained to make a product whether it is goods or services, ranging from handicrafts, bakery, laundry, and Barber. But in the implementation of entrepreneurship programs such as handicrafts encountered a dead end because of not finding the right market. It takes a marketing strategy that is able to increase the selling power of the resulting product. Increase from product quality, product sales price, product distribution, and product promotion. The journal's writing aims to determine the right marketing strategy to increase the sales of convict production. The journal's writing uses a library of libraries aimed at identifying the right marketing strategy to increase the sales of convict production, and to determine the right strategy for product quality improvement.